2015
DOI: 10.1167/15.11.17
|View full text |Cite
|
Sign up to set email alerts
|

The effects of grouping on speed discrimination thresholds in adults, typically developing children, and children with autism

Abstract: Adult observers show elevated speed discrimination thresholds when comparing the speeds of objects moving across a boundary compared to those moving parallel to a boundary (Verghese & McKee, 2006)-an effect that has been attributed to grouping processes in conjunction with a prior for smooth motion. Here, we extended Verghese and McKee's (2006) paradigm to typically developing children (n = 35) and children with autism (n = 26) and compared their performance with that of typical adults (n = 19). Speed discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…We propose, therefore, that the considerable individual differences in psychophysical estimates reflect more than just measurement error. Such individual differences could also help explain previous discrepant results, including those between Verghese and McKee ( 2006 ) and Manning et al ( 2015 ). Generally, studies of speed discrimination may require larger participant samples than the common practice in visual psychophysics.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We propose, therefore, that the considerable individual differences in psychophysical estimates reflect more than just measurement error. Such individual differences could also help explain previous discrepant results, including those between Verghese and McKee ( 2006 ) and Manning et al ( 2015 ). Generally, studies of speed discrimination may require larger participant samples than the common practice in visual psychophysics.…”
Section: Discussionmentioning
confidence: 88%
“…Verghese and McKee reported discrimination thresholds that were equally low in the two cases. Manning, Neil, Karaminis, and Pellicano ( 2015 ) used a similar display with adults, typical and autistic children, but did not replicate Verghese and McKee's result; for all three groups, thresholds for the split oblique motions were substantially higher than for the parallel (vertical or horizontal) motions. The interpretation of the results from both these studies is complicated by the fact that as well as difference in the relation between the directions of the motions being compared, the conditions also differed in the axis of motion, which was one of the cardinal axes in the parallel case, but oblique in the “split” case.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Most illusions also rely on structural priors, and show that such priors are often not very malleable. Despite findings of reduced susceptibility to (some) illusions (Mitchell, Mottron, Soulieres, & Ropar, 2010), several recent studies suggest that structural priors are actually intact in ASD (Croydon, Karaminis, Neil, Burr, & Pellicano, 2017; Manning, Neil, Karaminis, & Pellicano, 2015; Spanò, Peterson, Nadel, Rhoads, & Edgin, 2015).…”
mentioning
confidence: 97%
“…68,69 On the contrary, speed discrimination impairments seem to be preserved in, at least, some of these disorders. 70,71 Thus, it seems that speed discrimination deficits may represent more specific motion deficits in dyslexia than coherent motion deficits. Additionally, recent genetic studies showed that some motion deficits, including coherent motion but not speed discrimination, are particularly strong in dyslexic individuals with a deletion in intron 2 of the DCDC2 gene rather than in the whole dyslexic population.…”
Section: Discussionmentioning
confidence: 99%